FAKTOR YANG MEMPENGARUHI PEMBENTUKAN KRISTAL URIN PENGKONSUMSI AIR HUJAN DI KELURAHAN GUBUKUSUMA KOTA TIDORE KEPULAUAN - Rony Puasa; Febrianti Jakaria (Poltekkes Kemenkes Pakassar, 2020)
ABSTRACKBackground ; The ideal drinking water must be clear, colorless, tasteless, odorless and do not contain pathogenic germs. The use of water for drinking should meet health requirements, water that does not meet health requirements can cause kidney problems with the formation of crystals. Crystals that are commonly found in urine are calcium oxalate, triple phosphate, calcium phosphate and uric acid. One area in North Maluku Province where people still consume rain water as drinking, bathing and washing water is Gubukusuma Village, North Tidore District, Tidore Islands City. Aim ; identify the factors that can influence the formation of urine crystals in rain water consumption in the Gubukusuma Village. Method ; The research design used is a combination of survey and laboratory tests with the